Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1080/13880209.2020.1791192
|View full text |Cite|
|
Sign up to set email alerts
|

Caffeine reduces deficits in mechanosensation and locomotion induced by L-DOPA and protects dopaminergic neurons in a transgenic Caenorhabditis elegans model of Parkinson’s disease

Abstract: Context: L-DOPA is the first-line drug for Parkinson's disease (PD). However, chronic use can lead to dyskinesia. Caffeine, which is a known neuroprotectant, can potentially act as an adjunct to minimise adverse effects of L-DOPA. Objectives: This study determined changes in terms of neurodegeneration, locomotion and mechanosensation in Caenorhabditis elegans (Rhabditidae) strain UA57 overexpressing tyrosine hydroxylase (CAT-2) when treated with caffeine, L-DOPA or their combinations. Materials and methods: Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…This effect is reversed by concomitant exposure to adenosine, suggesting a conserved caffeine-AR pathway in the nematode ( 68 ). Of note, administration of 10 m m caffeine (the same concentration used in our experiments) to C elegans protects dopaminergic neurons from neurodegeneration elicited by excessive biosynthesis of endogenous L-DOPA ( 43 ), and improve aberrant locomotion induced by L-DOPA in a transgenic C. elegans model of PD ( 44 ). Specifically, Manalo et al.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This effect is reversed by concomitant exposure to adenosine, suggesting a conserved caffeine-AR pathway in the nematode ( 68 ). Of note, administration of 10 m m caffeine (the same concentration used in our experiments) to C elegans protects dopaminergic neurons from neurodegeneration elicited by excessive biosynthesis of endogenous L-DOPA ( 43 ), and improve aberrant locomotion induced by L-DOPA in a transgenic C. elegans model of PD ( 44 ). Specifically, Manalo et al.…”
Section: Discussionmentioning
confidence: 93%
“…5B ). For these experiments, the lowest effective m m concentration has been used since 10 m m caffeine already proved to protect dopaminergic neurons from dopamine-induced neurodegeneration ( 43 ) and to reduce aberrant locomotion induced by L-DOPA in a transgenic C. elegans model of Parkinson’s disease [PD; ( 44 )]. Automated recordings of C. elegans trajectories highlighted the beneficial effect of caffeine (10 m m ) on the hyperactive crawling of goa-1 [S47G] and goa-1 [A221D] mutants as well as of animals lacking goa-1 ( Supplementary Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the difference in expression levels of cat-2 and bas-1 may cause the accumulation of L-DOPA, a precursor of dopamine synthesis that is produced by the actions of the products of these two genes. To test this hypothesis, we measured the intensity of dopaminergic neurons in R02D3.7 mutants, as exogenous L-DOPA has been reported to damage dopaminergic neurons [43][44][45]. We found that the fluorescence intensity of dopaminergic neurons was 30% less in R02D3.7(ok1745) mutants than in wild-type animals (Figure 4E, compare left panel vs. middle panel in Figure 4F).…”
Section: R02d37 Downregulates the Expression Of Dopamine Metabolism-r...mentioning
confidence: 92%
“…31,32 In C. elegans, cat-2 overexpression is used as an endogenous model of L-DOPA exposure to replicate an increase in dopamine production; however, these animals show age-dependent dopaminergic neurodegeneration. 33,34 Taken together, previous studies have found that proper dopamine synthesis and sequestration is essential to maintaining neuronal health in C. elegans, and dysregulation of dopamine homeostasis can affect many behaviors in C. elegans including growth and reproduction.. In this study, we sought to determine whether endogenously increasing dopamine production through the overexpression of cat-2 could rescue the deficits identified in cat-1 null C. elegans.…”
Section: Introductionmentioning
confidence: 99%